Implementasi E-Recruitment Karyawan Kontrak pada PT Pegadaian Kanwil IX Jakarta 2 di Era Pasca Pandemi Covid-19 - Maya Sofiana; Endang Supriyadi; Ahmad Junaidi; Karlina Aulia Putri (CV ODIS, 2022)
The purpose of this study is to find out the description of the implementation of contract employee e-recruitment at PT Pegadaian Kanwil IX Jakarta 2 in the post-pandemic era of Covid-19. The research method used is qualitative method and descriptive approach. The e-recruitment process is carried out in several stages including the first stage, candidates are drawn by using the organization's reputation, product image, electronic technology and other methods to reach a wide range of potential applicants to the organization's website. The second stage, sorting applicants. The third stage, incoming electronic application letters must be managed quickly. Primary and secondary data collection techniques using in-depth interviews, observation, and documentation. This study uses the theory of the Rumangkit model. The implementation of e-recruitment for contract employees at PT Pegadaian Kanwil IX Jakarta 2 in the post-pandemic era of Covid-19 is carried out using Kalibrr